O ponto de vista nortista: Capistrano de Abreu e a Constituição do Campo Intelectual Cearense - Forte, Vinícius Limaverde (2011)
This study intent to discuss the relationship between the conception of Capistrano de Abreu about the constitution of Brazilian society under the Portuguese colonization and the emergence of an intellectual field in the second half of the 19th century in Ceará. According to Capistrano de Abreu the most important subject during the colonial period it was the occupation of the interior of Brazil, specially the colonization of the territory between the rivers São Francisco and Parnaíba. The livestock development has enabled the establishment of the settler and the emergence of "leather civilization" in backland. In parallel, several intellectuals also reflected about the importance of colonization of backland in the constitution of Ceará. Capistrano de Abreu knew the most part of these intellectuals and they often argued about the occupation of the backland. Thus, the focus in this dissertation is to analyze the exchange of ideas between theses intellectuals and Capistrano de Abreu. The result of this exchange is the creation of a “point of a view from the north” about the formation of Brazil